Studies on Synthesis, Method Development, Characterization and Antimicrobial Activities of Ibuprofen Lysinate - M.V. KUMUDHAVALLI; MARGRET CHANDIRA; D. SRIPRIYA; B.JAYAKAR (International Journal of Pharma and Bio Sciences, 2010)
The aim of the study is to Synthesis, Method Development, Characterisation and Antimicrobial activities of Ibuprofen lysinate. The following some of the important findings in the present study.Ibuprofen lysinate were synthesized in good yield.Compound exhibited good antimicrobial activity. Percentage recovery of Ibuprofen Lysinate is 99.2% by HPLC .The compound exhibited good antibacterial activity against Bacillus subtilis, Staphyloccus aureous, Escherrichia coli, Pseudomonas aeruginosa, and good antifungal activity against candida albicans.